2012
DOI: 10.1175/jas-d-12-0110.1
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint Sensitivity and Predictability of Tropical Cyclogenesis

Abstract: The sensitivity of tropical cyclogenesis and subsequent intensification is explored by applying small perturbations to the initial state in the presence of organized mesoscale convection and synoptic-scale forcing using the adjoint and tangent linear models for the Coupled Ocean-Atmosphere Mesoscale Prediction System (COAMPS). The forward, adjoint, and tangent linear models are used to compare and contrast predictability characteristics for the disturbance that became Typhoon Nuri and a nondeveloping organized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 70 publications
4
20
0
Order By: Relevance
“…In this study, only warm-rain processes are included to minimize the inherent nonlinearities associated with the microphysics, although the adjoint and tangent linear models include ice, snow, and graupel microphysical species (Doyle et al 2012). The decision points or switches that may result in discontinuities are identical in the nonlinear, tangent linear, and adjoint models (Zou et al 1993;Vukicevic and Errico 1993).…”
Section: B Adjoint and Tangent Linear Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, only warm-rain processes are included to minimize the inherent nonlinearities associated with the microphysics, although the adjoint and tangent linear models include ice, snow, and graupel microphysical species (Doyle et al 2012). The decision points or switches that may result in discontinuities are identical in the nonlinear, tangent linear, and adjoint models (Zou et al 1993;Vukicevic and Errico 1993).…”
Section: B Adjoint and Tangent Linear Modelsmentioning
confidence: 99%
“…The optimal perturbations derived from the adjoint gradients and evolved in the tangent linear and nonlinear models are used to evaluate the validity of the tangent linear approximation for the integration length (36 h) and resolutions considered in this study [see similar evaluation for this model in Doyle et al (2012) for a tropical application]. The nonlinear perturbation is defined as the difference between the nonlinear forecast from the control state and the nonlinear forecast from the perturbed state.…”
Section: A Nonlinear Model Simulationmentioning
confidence: 99%
“…The effect of moist physics was not considered in this study for the sake of maintaining realistic results in the adjoint model simulations. Sophisticated adjoint models now exist that can explicitly handle the physics of parameterized moist convection, including the WRF, COAMPS (e.g., Doyle et al 2012), and GEOS-5 (Holdaway and Errico 2014), and the inclusion of these moisture physics and their interaction with the barotropic growth mechanism in east Pacific tropical cyclogenesis is an area of further study. The results shown here omit the impact of moisture where moisture likely plays a significant role, and previous results using a similar technique with a moist adjoint have found moisture perturbations to be dominant (Doyle et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Application of adjoint models to TC development has largely been restricted to sensitivity of TC steering Wu et al 2007Wu et al , 2009Chen et al 2009;Hoover and Morgan 2010); this is at least partially due to the constraints of linearity and simplified moisture physics that limit the applicability of adjoint models to tropical dynamics, though adjoint techniques have been applied to problems surrounding TC structure and genesis in more recent years as models have grown more sophisticated (Doyle et al 2012;Lang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Socalled evolved singular vectors have been shown to be almost entirely defined by these translational dipoles (Kim and Jung 2009), and in an idealized, barotropic model, the first two of the leading three TESVs were found to be focused on track divergences in perpendicular directions, with vortex structure changes not being relevant until the third singular vector (Yamaguchi et al 2011). It may be found that, in order to investigate the sensitivity of TC intensity more closely, one must radically alter the TESV or choose a more focused measure of sensitivity (e.g., Doyle et al 2012). Strategies for focusing adaptive observing guidance on nontrack-related aspects of the forecast (e.g., intensity) remain a relatively unexplored area of research and demands further study.…”
Section: Discussionmentioning
confidence: 99%